The Mediating Role of Psychological Wellbeing in the Relationship Between Defense Mechanisms and Therapeutic Alliance Among Therapists and Psychiatric Nurses - Saba Jafari; Amin Rafiepour; Afsaneh Taheri; Mehrdad Sabet (Iran University of Medical Sciences, 2022)
Background: The effectiveness of psychotherapy relies on the therapeutic alliance, so it is essential to identify the variables related to this concept. The present study investigated the relationship between defense mechanisms and therapeutic alliance with the mediating role of psychological wellbeing in therapists and psychiatric nurses. Methods: This research was a descriptive-correlational study that adopted Structural Equation Modeling (SEM). The statistical population comprised all therapists, psychiatric nurses, and counselors licensed by the Psychology and Counseling Organization of Iran in 2019. A sample of 255 was selected via the convenience sampling method. The research instruments included the defense style questionnaire, Ryff's psychological wellbeing scale (short form), and the working alliance inventory (short form). The obtained data were analyzed by the Pearson correlation coefficient and path analysis in AMOS software v. 24. Results: Immature (β=-0.35, P<0.001) and neurotic defense mechanisms (β=-0.22, P<0.001) demonstrated significant negative correlations with the therapeutic alliance, while mature defense mechanisms (β=0.38, P<0.001) and psychological wellbeing (β=0.24, P<0.001) showed significant positive correlations with therapeutic alliance. The path analysis revealed the mediating role of psychological wellbeing in the relationships between immature (β=-0.11, P<0.01), mature (β=0.14, P<0.01), and neurotic (β=-0.09, P<0.01) defense mechanisms with therapeutic alliance. Conclusion: The present study results confirmed the model's goodness of fit. Therapists' defense mechanisms and psychological wellbeing should be taken into account when designing measures to improve the psychotherapy and counseling outcome.